Optimalisasi Penggunaan Alat Berat dalam Pekerjaan Timbunan Jalan Tol Patimban Paket 02 - Athaya Zhafirah; Algi Muhaemin; Rudy Febrijanto; Madi Hermadi (Jurnal Konstruksi, 2026)
The Patimban Toll Road Project Package 02 at STA 21+800–23+600 is part of a National Strategic Project (PSN) that requires high efficiency, particularly in large-volume embankment works. This study aims to analyze the productivity of heavy equipment used in embankment operations in order to determine an optimal equipment utilization plan in terms of time and cost. The scientific contribution of this research lies in the development of an approach for planning the number of equipment units based on actual field productivity combined with operational cost analysis, which can serve as a reference for heavy equipment management in large-scale infrastructure projects. The results show that a combination of 6 units of Komatsu PC200 excavators, 38 units of Isuzu dump trucks, 6 units of Zomlion ZD170G bulldozers, 5 units of sheep foot rollers, and 5 units of vibratory rollers is capable of completing an embankment volume of 372,714 m³ within 90 working days, with a total rental cost of IDR 191,644,520 per day.